Biodegradable PBAT / bamboo charcoal master batch and preparation method thereof
By microwave-assisted heating modification and polyacid grafting treatment on bamboo charcoal, the problem of poor compatibility between PBAT materials and bamboo charcoal-based fillers is solved, and the mechanical properties and moisture-heat resistance of the composite material are significantly improved.
Patent Information
- Application Number
- CN202510224795.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The compatibility and dispersion effect of existing PBAT materials with bamboo charcoal-based fillers are poor, resulting in low addition of bamboo charcoal fillers and poor mechanical properties of composite materials.
The bamboo charcoal is modified by microwave-assisted heating method combined with strong oxidizing agent to increase the acidic oxygen-containing functional groups on the surface, and then the bamboo charcoal is grafted and modified with polybasic acid as a compatible agent to improve the compatibility and dispersion of bamboo charcoal with PBAT.
The compatibility and dispersion of bamboo charcoal and PBAT are improved, the mechanical properties and high temperature and humidity resistance of composite materials are improved, and the cost is reduced.
Smart Images

Figure CN119684765A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biodegradable plastics, and in particular relates to a biodegradable PBAT / bamboo charcoal masterbatch and a preparation method thereof. Background Art
[0002] Plastic products are widely used in packaging, construction, agriculture, automobiles, medical and other fields due to their lightness, durability and low cost. However, traditional plastic products do not have the ability to degrade, so the large-scale production and use of plastic products have brought about environmental pollution problems. Plastics that are not easily degradable accumulate in the natural environment, causing long-term effects on soil, water sources, wildlife and human health. Biodegradable plastic products refer to plastics whose various properties can meet the requirements of use, whose properties do not change during the shelf life, and which can be degraded into harmless substances that can be absorbed by nature under natural conditions after being discarded.
[0003] Polybutylene terephthalate-adipate (PBAT) is a fully biodegradable aromatic copolymer with mechanical properties comparable to those of low-density polyethylene (LDPE). It has good toughness, ductility, film-forming properties, high impact strength, and good melt processability, and can be widely used in packaging materials. However, PBAT has defects such as low strength, poor creep resistance, low modulus, and high cost, which limit its application. Adding natural fillers is an effective way to increase the modulus and creep resistance of PBAT and reduce its cost. Bamboo charcoal comes from low-cost bamboo felling and processing residues. It has a high-strength carbon skeleton and a hard texture. It can also generate a rich multi-level pore structure through the control of the carbonization process. In view of the unique pore structure, hydrophobic surface, and low cost of bamboo charcoal, bamboo charcoal has great potential as a powder filler for compounding with biodegradable polymer materials. This type of composite material can reduce costs. By increasing the amount of inorganic powder in the material, the modulus, flame retardancy, and antistatic properties of the composite material can be significantly improved. At present, bamboo charcoal and PBAT composite materials have poor compatibility and insufficient matrix dispersion. As a result, the addition of bamboo charcoal leads to a serious decrease in the mechanical properties of the composite materials.
[0004] Patent CN113773626A discloses an environmentally friendly degradable masterbatch, in which less bamboo charcoal powder is added, which cannot effectively reduce the cost, and needs to be matched with modified corn starch, and the preparation process is relatively complicated. In addition, since the carbonization temperature of the added bamboo charcoal is not controlled, the shading effect of the composite material prepared when used as a black masterbatch cannot be guaranteed. CN119081440A discloses a bamboo-based degradable material, which is composed of the following components in parts by weight: 35-45 parts of bamboo powder, 20-25 parts of polylactic acid, 20-25 parts of PBAT, 5-10 parts of compatibilizer, and 5-10 parts of PBS, and the compatibilizer is a maleic anhydride grafted compatibilizer. CN117624853A discloses a bamboo powder modified polylactic acid-based biodegradable composite material, including polylactic acid, PBAT resin, modified bamboo powder, modified reinforcing filler, antioxidant, lubricant and plasticizer; the modified bamboo powder is obtained by sequentially coating and modifying bamboo powder with polydopamine and grafting with maleic anhydride; the modified reinforcing filler is obtained by surface modification of calcium carbonate powder with coconut oil and stearic acid. Patent CN 101818414 A uses an aluminate coupling agent to modify bamboo charcoal to increase compatibility with polypropylene, and uses liquid wax and zinc stearate as dispersants to promote the dispersion of bamboo charcoal. The coupling agent has limited modification effect on low-density bamboo charcoal and cannot effectively promote the formation of an effective interface layer between bamboo charcoal and matrix resin. The traditional dispersant has poor plasticizing and dispersing effect at high bamboo charcoal content, and cannot effectively avoid the agglomeration and dispersion of bamboo charcoal, so the performance of the obtained composite material is low. Moreover, the bamboo charcoal powder content used in this patent is low, which cannot prove that it can still be effective at high bamboo charcoal powder content. Summary of the invention
[0005] In order to solve the compatibility of PBAT materials and bamboo charcoal-based fillers in the prior art, the dispersion effect is poor, resulting in low addition of bamboo charcoal fillers and poor mechanical properties of composite materials. The present invention uses a microwave-assisted heating method combined with a strong oxidant to modify bamboo charcoal, so that the number of acidic oxygen-containing functional groups such as carboxyl groups on the surface is increased, and then a polyacid is added as a compatibilizer to graft the bamboo charcoal to obtain grafted bamboo charcoal, so that the surface of the bamboo charcoal and the PBAT can form an interpenetrating interface layer, and an interlocking structure is formed between the two, thereby improving the compatibility and dispersibility of bamboo charcoal and PBAT, thereby improving the mechanical properties of the bamboo charcoal / PBAT masterbatch and reducing the cost.
[0006] Specifically, the present invention provides the following technical solutions to solve the above technical problems: A biodegradable PBAT / bamboo charcoal masterbatch comprises the following raw materials in parts by weight: 100 parts of polybutylene terephthalate-adipate (PBAT), 20-30 parts of polybutylene succinate, 10-30 parts of modified bamboo charcoal powder, and 0.2-0.4 parts of a chain extender; the modified bamboo charcoal powder is obtained by sequentially subjecting the bamboo charcoal powder to sulfate treatment, microwave-assisted reaction, and grafting agent modification, wherein the grafting agent comprises a polyacid and an epoxy compound.
[0007] Furthermore, the weight average molecular weight of the polybutylene terephthalate-adipate is 200,000-400,000; the molecular weight of the polybutylene succinate is 200,000-300,000; the chain extender is selected from one or more of 2, 4-toluene diisocyanate, pyromellitic anhydride, ethylene-methacrylate glycidyl copolymer, styrene-methacrylate glycidyl copolymer, 2, 5-dimethyl-2, 5-di(tert-butylperoxy)hexane. The persulfate is selected from at least one of sodium persulfate, potassium persulfate, and ammonium persulfate.
[0008] Furthermore, the polyacid is selected from at least one of tannic acid, itaconic acid, and succinic acid; the epoxy compound is selected from at least one of glycidyl acrylate, glycidyl methacrylate, styrene-glycidyl methacrylate copolymer, and methyl methacrylate-glycidyl methacrylate copolymer.
[0009] Furthermore, the grafting agent is a compound of tannic acid, itaconic acid and / or succinic acid, and epoxy compound in a mass ratio of 3-5:3-5:1-2. The above-mentioned compounded grafting agent can not only improve the mechanical properties of the composite material, but also significantly improve the high temperature and high humidity resistance of the composite material, further broadening the scope of application of such composite biodegradable materials. It should be noted that the compounded grafting agent should be used in a reasonable amount ratio, otherwise it may have a certain adverse effect on the mechanical properties and / or degradability.
[0010] Furthermore, the bamboo charcoal powder is obtained by carbonizing low-density bamboo species, and the density of the low-density bamboo species is 0.33-0.5 g / cm 3 , such as yellow-stemmed black-feeding bamboo (0.41g / cm 3 )、Yazhu(0.33g / cm 3 )、Zhejiang light bamboo(0.43g / cm 3). The carbonization process is well known in the art. The low-density bamboo material is cut into bamboo pieces of 1-5 cm, and pre-oxidized at 300-400 ° C (air flow rate 0.05-0.1 L / min) for 0.5-1h; after pre-oxidation, switch to protective nitrogen gas flow, flow rate 0.2-0.5 L / min, heating rate 5-20 ° C / min, heat to 800-1100 ° C, carbonize for 1-2h; after carbonization, grind to 200-400 mesh, and after grinding, further use air flow mill for ultrafine grinding to 1000-2000 mesh to obtain bamboo charcoal powder. The density of the obtained bamboo charcoal powder is 0.5-0.7g / cm 3 , with a specific surface area of 500-700 m² / g.
[0011] The bamboo charcoal powder used in the present invention is a low-density carbon powder material with a density of 0.5-0.7 g / cm 3 , much lower than traditional petroleum-based carbon powder (1.5-1.85 g / cm 3 ). Low-density carbon powder can reduce the overall mass of the material while maintaining the same volume filling rate, improve filling efficiency, effectively build a conductive percolation network, and the increase in specific surface area also provides more reactive sites. However, low-density carbon powder materials also bring some challenges. Compared with high-density carbon powder, it is more difficult to disperse and more prone to agglomeration, and the compatibility problem with PBAT matrix materials is also more difficult to solve. The present invention solves the above problems by modifying bamboo charcoal powder.
[0012] Furthermore, the modified bamboo charcoal powder is prepared by a preparation method comprising the following steps: (S1) immersing the bamboo charcoal powder in a 0.5-1.0 mol / L persulfate aqueous solution at a concentration of 4-10 times by weight for 5-20 h, and then subjecting the mixture to ultrasonic treatment for 1-2 h to obtain a mixed solution; (S2) reacting the mixed solution under microwave conditions for 10-20 min, filtering, washing the solid phase, and drying to obtain surface-treated bamboo charcoal powder; (S3) The surface-treated bamboo charcoal powder is placed in a grafting agent solution and reacted at 60-80° C. to obtain modified bamboo charcoal powder.
[0013] Furthermore, in step (S1), the persulfate is selected from at least one of sodium persulfate, potassium persulfate and ammonium persulfate; and the ultrasonic treatment is performed at a power of 100-200 W and a frequency of 60-180 kHz.
[0014] Furthermore, in step (S2), washing is performed with water until the washing liquid is neutral; the microwave condition power is 600-1000W, such as 800W, 900W. The purpose of the microwave treatment reaction is to break up the microporous structure of the bamboo charcoal, further reduce the dispersed particle size, increase the porosity of the bamboo charcoal, and expand the pore size. The structural change helps to increase the specific surface area and adsorption capacity of the bamboo charcoal, thereby enhancing its reaction to the oxidant. At the same time, microwave-assisted heating provides more uniform energy supply and faster energy transfer to the interior of the bamboo charcoal, causing the bamboo charcoal particles to heat up rapidly. This helps to accelerate the reaction rate and efficiency of the oxidant with the surface of the bamboo charcoal, increase the reaction process, and thereby obtain more acidic functional groups, i.e., the subsequent reaction sites with the grafting modifier.
[0015] Further, in step (S3), the grafting agent solution is obtained by dissolving the grafting agent in an organic solvent, the organic solvent is selected from at least one of ethanol, ethyl acetate, dichloromethane, and chloroform, and the concentration of the grafting agent solution is 20-30wt%. The mass ratio of the surface-treated bamboo charcoal powder to the grafting agent solution is 1:6-10; the reaction time is 1-2h, and after the reaction is completed, filtering, washing, and drying are performed to obtain modified bamboo charcoal powder.
[0016] The modified bamboo charcoal powder of the present invention is obtained by sequentially subjecting low-density bamboo charcoal powder to oxidation, microwave reaction, and grafting modification. The surface of the modified bamboo charcoal powder has abundant functional groups, significantly improves the compatibility with the PBAT material, and enhances the mechanical properties of the composite material. The combination of two polyacids and an epoxy compound as a grafting agent can significantly improve the mechanical properties of the material, especially improve the moisture and heat resistance of the material.
[0017] The present invention also provides a method for preparing a biodegradable PBAT / bamboo charcoal masterbatch, comprising the following steps: polybutylene terephthalate-adipate (PBAT), polybutylene succinate, bamboo charcoal powder and a chain extender are uniformly mixed in an internal mixer to obtain a biodegradable PBAT / bamboo charcoal masterbatch.
[0018] Furthermore, the preparation method of the biodegradable PBAT / bamboo charcoal masterbatch comprises the following steps: Polybutylene terephthalate-adipate (PBAT) and polybutylene succinate are added to an internal mixer and mixed for 1-5 min at 150-180 ° C and 60-100 rpm. Modified bamboo charcoal powder is added and mixed for 1-5 min. Finally, a chain extender is added and mixed for 3-10 min. After mixing, the mixture is cooled to room temperature to obtain a biodegradable PBAT / bamboo charcoal masterbatch.
[0019] Compared with the prior art, the modified bamboo charcoal powder prepared by the present invention through specific raw materials and methods has significantly improved interfacial compatibility with the PBAT substrate and matrix dispersibility, and improved the mechanical properties of the composite material. In addition, the damp heat aging resistance of the composite material is improved by compounding the modifier in a specific proportion. After the obtained composite material is placed at high temperature and high humidity of double 85 for 30 days, the mechanical property loss is very low. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a polarizing microscope picture of the composite material obtained in Example 3; Figure 2 is a scanning electron microscope image of the composite material obtained in Example 3. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further explained and illustrated by specific embodiments below.
[0022] The bamboo charcoal powder used in the present invention is a kind of bamboo (0.33g / cm 3 ) cut into 1-2cm bamboo slices, baked until the moisture content is less than 5%, first pre-oxidized at 400℃ for 1h at an air flow rate of 0.1L / min, then switched to 0.4L / min nitrogen, heated to 1000℃ at a heating rate of 15℃ / min, and kept warm for 2h to complete carbonization. After carbonization, the carbon material was crushed to 400 mesh by Raymond mill, and then ground to 1500 mesh by air jet mill to obtain bamboo charcoal powder with a density of 0.52g / cm 3 .
[0023] The weight average molecular weight of butylene terephthalate (PBAT) is about 260,000, and the melt index is 3.1 g / 10 min.
[0024] The weight average molecular weight of polybutylene succinate is about 240,000, and the melt index is 6.8 g / 10min.
[0025] Preparation Example 1 (S1) 100 parts by weight of bamboo charcoal powder is immersed in 500 parts by weight of 0.9 mol / L potassium persulfate solution, stirred evenly and then soaked at room temperature for 10 hours, and then the mixture is placed in an ultrasonic washer and ultrasonicated at an ultrasonic frequency of 100 kHz and an ultrasonic power of 120 W for 2 hours to obtain a mixed solution; (S2) placing the mixed solution in a quartz glass reactor, placing it in a microwave oven, reacting it at a microwave power of 800 W for 10 minutes, filtering, washing the solid phase with distilled water until it is neutral, placing it in a drying oven, and drying it at 120° C. to constant weight to obtain surface-treated bamboo charcoal powder; (S3) adding a grafting agent to dichloromethane and stirring vigorously for 5 minutes to prepare a 20wt% grafting agent solution, wherein the grafting agent is a compound of tannic acid, itaconic acid, and glycidyl methacrylate in a mass ratio of 3:3:1, and the surface-treated bamboo charcoal powder obtained in step S2 is placed in the grafting agent solution and stirred, and the weight ratio of the surface-treated bamboo charcoal to the grafting agent solution is 1:6. The mixture is stirred and reacted in a water bath at 80°C until the dichloromethane is completely volatilized, first washed with alcohol, then washed with water, and dried in an oven at 100°C to obtain modified bamboo charcoal powder.
[0026] Preparation Example 2 The other conditions are the same as those in Preparation Example 1, except that in step (S3), the grafting agent is tannic acid, succinic acid, and glycidyl methacrylate in a mass ratio of 5:5:2.
[0027] Preparation Example 3 The other conditions are the same as those in Preparation Example 1, except that in step (S3), the grafting agent is a mixture of tannic acid and succinic acid in a mass ratio of 1:1.
[0028] Preparation Example 4 The other conditions are the same as those in Preparation Example 1, except that in step (S3), the grafting agent is glycidyl methacrylate.
[0029] Preparation Example 5 The other conditions are the same as those in Preparation Example 1, except that in step (S3), the grafting agent is a mixture of succinic acid and glycidyl methacrylate in a mass ratio of 3:1.
[0030] Preparation Example 6 The other conditions are the same as those in Preparation Example 1, except that in step (S3), the grafting agent is a mixture of tannic acid and glycidyl methacrylate in a mass ratio of 3:1.
[0031] Comparative Preparation Example 1 (S1) 100 parts by weight of bamboo charcoal powder is immersed in 500 parts by weight of 0.9 mol / L potassium persulfate solution, stirred evenly and then soaked at room temperature for 10 hours, then the mixture is placed in an ultrasonic washing machine, ultrasonicated at an ultrasonic frequency of 100 kHz and an ultrasonic power of 120 W for 2 hours, the obtained bamboo charcoal powder is filtered, washed, and dried to obtain oxidized bamboo charcoal powder; (S2) adding a grafting agent to dichloromethane and stirring vigorously for 5 minutes to prepare a 20wt% grafting agent solution, wherein the grafting agent is a compound of tannic acid, itaconic acid, and glycidyl methacrylate in a mass ratio of 3:3:1, and the oxidized bamboo charcoal powder obtained in step S1 is placed in the grafting agent solution and stirred, and the weight ratio of the surface-treated bamboo charcoal to the grafting agent solution is 1:6, and the reaction is stirred in a water bath at 80°C until the dichloromethane is completely volatilized, first washed with alcohol, then washed with water, and dried in an oven at 100°C to obtain modified bamboo charcoal powder. That is, compared with Preparation 1, the microwave reaction of step (S2) is not performed.
[0032] Comparative Preparation Example 2 The other conditions are the same as those in Preparation Example 1, except that in step (S3), the grafting agent is maleic anhydride grafted polylactic acid (PLA-g-St / MAH, purchased from Xi'an Qiyue Biology).
[0033] Example 1 100 parts by weight of butylene terephthalate-adipate (PBAT) and 30 parts by weight of polybutylene succinate were placed in an internal mixer at 150° C. and a mixing speed of 60 rpm for 1 min, and then 10 parts by weight of the modified bamboo charcoal powder prepared in Preparation Example 1 were added, mixed at 60 rpm for 2 minutes, and then 0.2 parts by weight of a chain extender 2,4-toluene diisocyanate was added, and mixing was continued at 60 rpm for 4 min. After mixing, the blend was cut into small pieces and directly cooled in air at room temperature to obtain the bamboo charcoal / PBAT composite material provided by the present invention.
[0034] Example 2 The other conditions were the same as those in Example 3, except that the amount of the modified bamboo charcoal powder prepared in Preparation Example 1 was 20 parts by weight.
[0035] Example 3 The other conditions were the same as those in Example 3, except that the amount of modified bamboo charcoal powder prepared in Preparation Example 1 was 30 parts by weight.
[0036] Figure 1 This is a polarizing microscope picture of the composite material obtained in Example 3, which can show from the side that the bamboo charcoal is evenly dispersed in the matrix. Figure 2 This is a scanning electron microscope image of the composite material obtained in Example 3. The boundary between bamboo charcoal and PBAT is not obvious, indicating that a mutually penetrating interface layer is formed and the interface compatibility is very good.
[0037] Example 4 The other conditions were the same as those in Example 3, except that the modified bamboo charcoal powder prepared in Preparation Example 1 was replaced by the modified bamboo charcoal powder prepared in Preparation Example 2.
[0038] Example 5 The other conditions are the same as those in Example 3, except that the modified bamboo charcoal powder prepared in Preparation Example 1 is replaced by the modified bamboo charcoal powder prepared in Preparation Example 3.
[0039] Example 6 The other conditions were the same as those in Example 3, except that the modified bamboo charcoal powder prepared in Preparation Example 1 was replaced by the modified bamboo charcoal powder prepared in Preparation Example 4.
[0040] Example 7 The other conditions were the same as those in Example 3, except that the modified bamboo charcoal powder prepared in Preparation Example 1 was replaced by the modified bamboo charcoal powder prepared in Preparation Example 5.
[0041] Example 8 The other conditions were the same as those in Example 3, except that the modified bamboo charcoal powder prepared in Preparation Example 1 was replaced by the modified bamboo charcoal powder prepared in Preparation Example 6.
[0042] Comparative Example 1 The other conditions were the same as those in Example 3, except that the modified bamboo charcoal powder prepared in Preparation Example 1 was replaced with the modified bamboo charcoal powder prepared in Comparative Preparation Example 1 of equal weight (ie, 30 parts by weight).
[0043] Comparative Example 2 The other conditions were the same as those in Example 3, except that the modified bamboo charcoal powder prepared in Preparation Example 1 was replaced by the modified bamboo charcoal powder prepared in Comparative Preparation Example 2 with an equal mass (i.e., 30 parts by mass).
[0044] Comparative Example 3 The other conditions were the same as those in Example 3, except that the modified bamboo charcoal powder prepared in Preparation Example 1 was replaced by an equal mass (ie, 30 parts by mass) of untreated bamboo charcoal powder.
[0045] Application Examples The composite materials obtained in the above examples and comparative examples were subjected to the following performance tests, and the results are shown in Table 1 below.
[0046] 1. The composite material was pressed into a sheet on a flat vulcanizer at 150°C and 10MPa, and then quickly placed in a cold press and cooled to room temperature at 2MPa to obtain a blended material sheet for testing. The sheet was cut into a dumbbell shape and the tensile strength and elongation at break of the blend were tested according to standard GB / T 1040.1-2018.
[0047] 2. Limiting oxygen index (LOI): The obtained blend was pressed into a sheet on a flat vulcanizer at 150°C and 10MPa, and then quickly placed in a cold press and cooled to room temperature at 2MPa to obtain a blended material sheet for testing. The sheet was cut into 150mm×10mm×4mm and the limiting oxygen index of the blend was tested according to standard GB / T 2406-2008.
[0048] 3. High temperature and high humidity resistance: After the composite material is placed at 85°C and 85RH% for 30 days, the tensile strength and elongation at break are retested, and the tensile strength retention rate and elongation at break retention rate are calculated.
[0049] 4. Area resistivity: The composite material was compression molded at 180°C and 10 MPa for 10 min and cooled under pressure to obtain a sheet with a specification of 120 mm×100 mm×2 mm. The area resistivity of the composite material was measured at room temperature using a high resistance meter. Five groups were tested in parallel and the result was taken as the average of the five groups of data.
[0050] Table 1 Performance test of bamboo charcoal / PBAT composite materials .
Claims
1. A biodegradable PBAT / bamboo charcoal masterbatch, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polybutylene terephthalate-adipate (PBAT), 20-30 parts of polybutylene succinate, 10-30 parts of modified bamboo charcoal powder, and 0.2-0.4 parts of a chain extender; the modified bamboo charcoal powder is obtained by sequentially subjecting the bamboo charcoal powder to persulfate treatment, microwave-assisted reaction, and grafting agent modification, wherein the grafting agent comprises a polyacid and an epoxy compound.
2. The biodegradable PBAT / bamboo charcoal masterbatch according to claim 1, characterized in that: The weight average molecular weight of the polybutylene terephthalate-adipate is 200,000-400,000; the molecular weight of the polybutylene succinate is 200,000-300,000; the chain extender is selected from one or more of 2, 4-toluene diisocyanate, pyromellitic anhydride, ethylene-methacrylate glycidyl copolymer, styrene-methacrylate glycidyl copolymer, and 2, 5-dimethyl-2, 5-di(tert-butylperoxy)hexane; the persulfate is selected from at least one of sodium persulfate, potassium persulfate, and ammonium persulfate.
3. The biodegradable PBAT / bamboo charcoal masterbatch according to claim 1, characterized in that: The polyacid is selected from at least one of tannic acid, itaconic acid and succinic acid; the epoxy compound is selected from at least one of glycidyl acrylate, glycidyl methacrylate, styrene-glycidyl methacrylate copolymer and methyl methacrylate-glycidyl methacrylate copolymer.
4. The biodegradable PBAT / bamboo charcoal masterbatch according to claim 1, characterized in that: The grafting agent is a compound of tannic acid, itaconic acid and / or succinic acid and epoxy compound in a mass ratio of 3-5:3-5:1-2.
5. The biodegradable PBAT / bamboo charcoal masterbatch according to claim 1, characterized in that: The bamboo charcoal powder is obtained by carbonizing low-density bamboo species, and the density of the low-density bamboo species is 0.33-0.5 g / cm 3 The density of the bamboo charcoal powder obtained after carbonization is 0.5-0.7g / cm 3 , with a specific surface area of 500-700 m² / g.
6. The biodegradable PBAT / bamboo charcoal masterbatch according to claim 1, characterized in that: The modified bamboo charcoal powder is prepared by a preparation method comprising the following steps: (S1) immersing the bamboo charcoal powder in a 0.5-1.0 mol / L strong oxidant aqueous solution at a concentration of 4-10 times by weight for 5-20 h, and then subjecting the mixture to ultrasonic treatment for 1-2 h to obtain a mixed solution; (S2) reacting the mixed solution under microwave conditions for 10-20 min, filtering, washing the solid phase, and drying to obtain surface-treated bamboo charcoal powder; (S3) The surface-treated bamboo charcoal powder is placed in a grafting agent solution and reacted at 60-80° C. to obtain modified bamboo charcoal powder.
7. The biodegradable PBAT / bamboo charcoal masterbatch according to claim 6, characterized in that: In step (S1), the ultrasonic treatment is performed at a power of 100-200 W and a frequency of 60-180 kHz; and / or In step (S2), the microwave condition power is 600-1000W; washing is washing with water until the washing liquid is neutral.
8. The biodegradable PBAT / bamboo charcoal masterbatch according to claim 6, characterized in that: In step (S3), the grafting agent solution is obtained by dissolving the grafting agent in an organic solvent, the organic solvent is selected from at least one of ethanol, ethyl acetate, dichloromethane, and chloroform, and the concentration of the grafting agent solution is 20-30wt%; the mass ratio of the surface-treated bamboo charcoal powder to the grafting agent solution is 1:6-10; the reaction time is 1-2h, and after the reaction is completed, filtering, washing, and drying are performed to obtain modified bamboo charcoal powder.
9. The method for preparing the biodegradable PBAT / bamboo charcoal masterbatch according to any one of claims 1 to 8, characterized in that: The following steps are involved: Polybutylene terephthalate-adipate, polybutylene succinate, bamboo charcoal powder and chain extender are uniformly mixed in an internal mixer to obtain biodegradable PBAT / bamboo charcoal masterbatch.
10. The preparation method according to claim 9, characterized in that: The following steps are involved: Polybutylene terephthalate-adipate and polybutylene succinate are added to an internal mixer, mixed for 1-5 minutes at 150-180°C and 60-100 rpm, modified bamboo charcoal powder is added, and mixing is continued for 1-5 minutes. Finally, a chain extender is added and mixing is continued for 3-10 minutes. After mixing, the mixture is cooled to room temperature to obtain a biodegradable PBAT / bamboo charcoal masterbatch.
Citation Information
Patent Citations
Nanometer-modified bamboo carbon polypropylene non-woven fabric
CN101818414A
Environment-friendly degradable master batch as well as preparation method and application thereof
CN113773626A
Bamboo powder modified polylactic acid-based biodegradable composite material and preparation method thereof
CN117624853A
Moso bamboo-based degradable material and preparation process thereof
CN119081440A
Pretreatment preparation method of active carbon for supercapacitor
CN103539114A
Cited By
Degradable food contact material with heat-resistant and antibacterial functions and preparation method thereof
CN122188362A
Degradable food contact material with heat-resistant antibacterial function and preparation method thereof
CN122188362B